Analytical model for gyro-phase drift arising from abrupt inhomogeneity. (June 2014) - Walker, Jeffrey J.; Koepke, M. E.; Zimmerman, M. I.; Farrell, W. M.; Demidov, V. I.
<x content-type="archive" xml:space="preserve">Abstract</x> If a magnetized-orbit-charged grain encounters any abrupt inhomogeneity in plasma conditions during a gyro-orbit, such that the resulting in-situ equilibrium charge is significantly different between these regions (q1/q2 ~ 2, where q1 is the in-situ equilibrium charge on one side of the inhomogeneity, q2 is the in-situ equilibrium charge on the other side, and q1 < q2 < 0), then the capacitive effects of charging and discharging of the dust grain can result in a modification to the orbit-averaged grain trajectory, i.e. gyro-phase drift. The special case of q1/q2 is notioned for the purpose of illustrating the utility of the method. An analytical expression is derived for the grain velocity, assuming a capacitor approximation to the OML charging model. For cases in which a strong electric field suddenly appears in the wake or at the space-plasma-to-crater interface from solar wind and/or ultraviolet illumination and in which a magnetic field permeates an asteroid, comet, or moon, this model could contribute to the interpretation of the distribution of fields and particles.